A trust-based crowdfunding campaign marketing framework: theoretical underpinnings and big-data analytics practice. (2nd December 2021) - Baah-Peprah, Prince; Shneor, Rotem
Crowdfunding research often understates the campaign marketing dynamics that are at play. In this paper, we develop a trust-based crowdfunding campaign marketing framework (TCMF). Since trust underlies online transactions our framework highlights four trust conditions (trust deficit, information trust deficit, relationship trust deficit, and trust surplus) fundraisers face when launching their campaigns, each requiring a different marketing strategy (minimalist, technician, influencer, and innovator) for enhancing trust between fundraisers and prospective funders. Moreover, we compare the TCMF with earlier theoretical frameworks, while highlighting its unique contributions. Finally, we suggest the application of big data analytics in practical use of the TCMF.